Gamification for Young Learners: Transforming Motivation and English Language Skills through Collaborative-Competitive Learning among Junior High School Students at SMPN 5 Sungailiat- Bangka Belitung - Indriati, Titin; Veniati; Daya Wulandari; Riztamala Diana; Mildazani; Endah Arum Wangi; Decky Putra Revo (Society : Jurnal Pengabdian Masyarakat, 2026)
The development of digital technology has significantly influenced and changed the current educational practices, particularly language learning and instruction. However, English instruction at the Indonesian junior secondary school level continues to be predominantly teacher-dominated and frequently provides limited opportunities for interactive, student-centered engagement. A mixed-method approach was applied, including classroom observations, student questionnaires, as well as reflective discussions to examine the impact of the program. Purpose of the Study: This community service was designed to improve students’ learning motivation and English language competencies through the application of gamification-oriented collaborative-competitive learning. The program was carried out at SMP Negeri 5 Sungailiat, Bangka Belitung, involving 30 junior high school students participating in a series of interactive digital games, team-based activities, and point-based competitions integrated into English lessons focusing on past tense structures. Methods: A mixed-method approach was applied, including classroom observations, student questionnaires, as well as reflective discussions to examine the impact of the program. Results: The results revealed a significant improvement in students’ learning motivation, classroom participation, and vocabulary development related to past tense usage. The integration of collaborative and competitive gamification elements created a supportive yet dynamic learning environment, encouraging peer interaction while maintaining students’ enthusiasm through healthy competition. Accordingly, the findings indicate that digital gamification constitutes an effective instructional approach for improving English grammar learning among young learners. This study uniquely integrates collaborative-competitive gamification within a community service framework, offering a practical model for grammar instruction in junior high school EFL contexts.